Rituximab Plus Chemotherapy Provides No Clinical Benefit in a Peripheral T-Cell Lymphoma not Otherwise Specified with Aberrant Expression of CD20 and CD79a: A Case Report and Review of the Literature - Alessandro Mangogna; Maria Christina Cox; Luigi Ruco; Gianluca Lopez; Beatrice Belmonte; Arianna Di Napoli (Diagnostics, 2020)
Peripheral T-cell lymphoma, not otherwise specified (PTCL-NOS) is the most common entity of mature T-cell neoplasms. PTCL-NOS generally has an aggressive behavior and is often refractory to standard therapy. Only a few cases of PTCL with aberrant expression of B-cell antigens have been reported so far. This phenotypic aberrancy may lead to misdiagnosis as B-cell non-Hodgkin lymphomas and eventual inappropriate patient management, whereas in an accurately diagnosed PTCL, the presence of CD20 may appear as an appealing therapeutic target. In this setting, response to anti-CD20 monoclonal antibody in combination with chemotherapy has been poorly explored. We describe the case of a 59-year-old male diagnosed by a pathological and molecular approach as PTCL-NOS with aberrant co-expression of the B-cell antigens CD20 and CD79a, which proved non-responsive to the addition of rituximab to standard polychemotherapy. This case highlights that the presence of CD20 in PTCL may be misleading in the diagnosis and also act as a lure for the clinician to adopt a rituximab-based treatment, the effectiveness of which is undefined as the molecular mechanisms underlying B-cell marker expression in PTCL.